The Perspectives of Yoga in Maintaining Psycho-Social Health and Overall Well-Being - Rawat, Kalpana; Chandravanshi, Dushayant; Sahu, Vikas; Pedhekar, Sunanda R (Journal of Neonatal Surgery, 2025)
A journey with Yoga is a comprehensive discipline including physical techniques (asanas), regulation of breath (pranayama), meditation, and ethical instruction (yama-niyama). The basic objective of yoga is to attain harmony and balance among the mind, body, and spirit. Yoga's focus on truthfulness (Satya) and nonviolence (ahimsa) may inspire individuals to actively contribute to society by advocating for equality, justice, and peace. Yoga programs with a communal emphasis may serve as catalysts for social change. Yoga may serve as a bridge in areas where social tensions and conflicts are common by fostering communication and understanding. The philosophy of yoga promotes the existence of eight domains of growth, including physical, mental, social, and spiritual well-being. Additionally, yoga promotes self-awareness and acceptance by improving one’s mental health and cognitive stability. Yoga enhances social cohesion by cultivating a feeling of communal togetherness and common objectives and cultivating friendliness and amicability among individuals